Infant insurance: a preliminary study on the awareness of it among citizens of Kuala Lumpur / Mohamad Sabri Alias and Amirul Jafni Malin Jafri Malin - Alias, Mohamad Sabri; Jafri Malin, Amirul Jafni Malin (Faculty of Business and Management, 2013)
The topic on this research is a "Preliminary study on the awareness of it among citizens of Kuala Lumpur". this study identifies and determines factors that have significant influence awareness of Kuala Lumpur citizens towards infant insurance. the objective of this study is to determine level of awareness of infant insurance in Kuala Lumpur and also to examine most factor influence awareness of infant insurance in Kuala Lumpur. the rationale of this research to determine level of awareness of infant insurance in Kuala Lumpur. in our research, we focus more on the infant insurance which is one of the awareness among parents nowadays. for the consequences, it can really helped the parents to increase their level of awareness in order to avoid any unexpected event of the miscarriage or unhealthy baby after giving birth in the hospital as for the guidelines and having the safety precaution in the future.